Formation of students’ research abilities while studying the discipline "Optics" - Zhunussova R.А.; Seitkhanova, A.K.; Кissabekovа А.А.; Alina A.В. (Recent Contributions to Physics, 2023)
The article describes the methods for developing the research skills of future physics teachers in the process of studying optics at a university. The purpose of this study is to improve the research abilities of students in lectures, practical and laboratory classes in optics. In the course of pedagogical research, we developed a model for the formation of readiness for research activities in the school of future physics teachers and formed the criterion and tools for determining readiness, which were applied during the teaching of optics. And also, a number of pedagogical conditions are defined, which, in our opinion, form the research competencies of students. Methods of problem-based learning, practice-oriented learning, methods of analysis and synthesis, methods of observation were applied. The relevance of the research topic lies in the problem of preparing future teachers of physics for organizing research activities with schoolchildren. Therefore, we have developed and tested the educational and methodological complex "Optics", proposed methods, forms, criteria for evaluating the research skills of future physics teachers. The presented methodology for the formation of research competence can be used for teaching other basic disciplines. The results of the research will be relevant for teachers of pedagogical universities who are looking for effective ways to train future specialists who are able to qualitatively prepare students for research activities.